Is Standard Oral Dose Dexamethasone (6mg Once Daily) Prescribed For COVID-19 Pneumonitis Treating Autoimmune Haemolytic Anaemia Associated with COVID-19? A Case Series of Five Patients Providing Us with the Answer - Dr. Saquib Navid Siddiqui, (International Journal of Innovative Research in Medical Science, 2021)
Initially originating as an epidemic respiratory illness in Wuhan, China, COVID-19 eventually spread around the world and has now been declared as a global pandemic disease by the WHO. Our understanding of the pathophysiology of SARS-CoV-2 is evolving with each passage of days. Previously thought to be a respiratory illness resulting in pulmonary complications such as pneumonia, respiratory failure, and acute respiratory distress syndrome now have been found to be causing multiple extra-pulmonary pathologies which includes various degree of autoimmune disorders. Certain group of patients have been found to have autoimmune haemolytic anaemia triggered by COVID-19. We report a case series of five patients who developed COVID-19 induced AIHA which responded dramatically to oral dexamethasone (6mg once daily) initially prescribed for the deteriorating pulmonary function. Therefore, our intuition is dexamethasone prescribed for COVID-19 pneumonitis is beneficial for the rapid recovery of AIHA associated with COVID-19.